A simple novel technique for enteroatmospheric fistulae: silicone fistula plug - Ozer, M Tahir (Int Wound J, 2014)
Enteroatmospheric fistulae (EAFs), a rare condition that develops in patients treated with an open abdomen, present serious problems for the surgeon. There are no fixed algorithms for treatment of EAF, and treatment options are determined based on the experience of the surgeon and status of the patient. We developed a ‘suspended silicone fistula plug’ for treating a patient who developed an EAF after undergoing multiple operations in a short period of time. Used in conjunction with negative pressure wound therapy, application of this novel therapy resulted in EAF closure and patient discharge.